Multisensory integration and interactions across vision, hearing, and somatosensation in autism spectrum development and typical development. (10th October 2022) - Dwyer, Patrick; Takarae, Yukari; Zadeh, Iman; Rivera, Susan M.; Saron, Clifford D.
Abstract: Most prior studies of multisensory integration (MSI) in autism have measured MSI in only a single combination of modalities – typically audiovisual integration. The present study used onset reaction times (RTs) and 125-channel electroencephalography (EEG) to examine different forms of bimodal and trimodal MSI based on combinations of auditory (noise burst), somatosensory (finger tap), and visual (flash) stimuli presented in a spatially-aligned manner using a custom desktop apparatus. A total of 36 autistic and 19 non-autistic adolescents between the ages of 11–14 participated. Significant RT multisensory facilitation relative to summed unisensory RT was observed in both groups, as were significant differences between summed unisensory and multisensory ERPs. Although the present study's statistical approach was not intended to test effect latencies, these interactions may have begun as early as ∼45 ms, constituting "early" (<100 ms) MSI. RT and ERP measurements of MSI appeared independent of one another. Groups did not significantly differ in multisensory RT facilitation, but we found exploratory evidence of group differences in the magnitude of audiovisual interactions in ERPs. Future research should make greater efforts to explore MSI in under-represented populations, especially autistic people with intellectual disabilities and nonspeaking/minimally-verbal autistic people. Highlights: Both autistic and non-autistic adolescents exhibit multisensory facilitation of reaction times. Both autistic and non-autistic adolescents exhibit multisensory interactions in ERPs. Multisensory facilitation of reaction times does not significantly differ between groups. Audiovisual interactions in ERPs significantly differ between autism and typical development.